Fragility Index and Fragility Quotient in Randomized Controlled Trials on Corticosteroids in ARDS Due to COVID-19 and Non-COVID-19 Etiology - Maria Vargas (MDPI AG, 2021)
Background: The effectiveness of corticosteroids in acute respiratory distress syndrome (ARDS) and COVID-19 still remains uncertain. Since ARDS is due to a hyperinflammatory response to a direct injury, we decided to perform a meta-analysis and an evaluation of robustness of randomised clinical trials (RCTs) investigating the impact of corticosteroids on mortality in ARDS in both COVID-19 and non-COVID-19 patients. We conducted a systematic search of the literature from inception up to 30 October 2020, using the MEDLINE database and the PubMed interface. We evaluated the fragility index (FI) of the included RCTs using a two-by-two contingency table and the p-value produced by the Fisher exact test; the fragility quotient (FQ) was calculated by dividing the FI score by the total sample size of the trial. Results: Thirteen RCTs were included in the analysis; five of them were conducted in COVID-19 ARDS, including 7692 patients, while 8 RCTS were performed in non-COVID ARDS with 1091 patients evaluated. Three out of eight RCTs in ARDS had a FI > 0 while 2 RCTs out of five in COVID-19 had FI > 0. The median of FI for ARDS was 0.625 (0.47) while the median of FQ was 0.03 (0.014). The median of FI for COVID-19 was 6 (2) while the median of FQ was 0.059 (0.055). In this systematic review, we found that FI and FQ of RCTs evaluating the use of corticosteroids in ARDS and COVID-19 were low.